ANALISIS MOTIVASI BELAJAR MAHASISWA KEPERAWATAN DALAM PEMBELAJARAN DARING - Maemunah, Neni; Putri, Ronasari Mahaji (Care : Jurnal Ilmiah Ilmu Kesehatan, 2022)
The low learning motivation of students in online learning during the COVID-19 pandemic is a cause for concern. Various situations and conditions of students who are different, contribute to the emergence of low learning motivation. This study aims to analyze the learning motivation of nursing students at X University in Malang in online learning. The population is all students who are actively carrying out lectures, and are registered as students at University X Malang. A sample of 76 people was taken using the Slovin formula, with a simple random sampling technique. The student's learning motivation instrument uses a questionnaire of 34 questions that has been tested for reliability validity. Data analysis using univariate test. The results showed that 65.8% of students had good learning motivation, 59.2% of students each had expectations, a good learning environment and interest in learning, 67.1% of students had good learning goals, and 50 % of students have sufficient learning infrastructure during the COVID-19 pandemic. It is recommended that further researchers need to explore psychologically what students feel when doing online learning